2023
DOI: 10.1021/acs.est.3c00864
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)/Cu(II) Released by Cu Nanoparticles Revealed Differential Cellular Toxicity Related to Mitochondrial Dysfunction

Abstract: Cu-based nanoparticles (NPs) have been increasingly fabricated, and different Cu species (i.e., Cu+ and Cu2+) of these NPs are tuned to achieve differential physicochemical properties. Although ion release is one of the major toxic mechanisms of Cu-based NPs, differences in cytotoxicity between released Cu­(I) and Cu­(II) ions are largely unknown. In this study, the A549 cells exhibited a lower tolerance to Cu­(I) compared with Cu­(II) accumulation. Bioimaging of labile Cu­(I) indicated that the change of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The labile Cu­(I) content in cells at each cell cycle stage did not exhibit a uniform increasing trend under heightened Cu stress, suggesting a functional difference between those two forms (Figure S5). A recent study also found differential cellular toxicity of labile Cu­(I) and Cu­(II) using Cu-based nanoparticles, suggesting that labile Cu­(II) may influence the cell cycle regulation . Thus, we proposed that the heterogeneous resistance of algae at different cell cycle stages to Cu stress stems from their disparate sensitivities to the labile Cu­(II) pool.…”
Section: Results and Discussionmentioning
confidence: 72%
“…The labile Cu­(I) content in cells at each cell cycle stage did not exhibit a uniform increasing trend under heightened Cu stress, suggesting a functional difference between those two forms (Figure S5). A recent study also found differential cellular toxicity of labile Cu­(I) and Cu­(II) using Cu-based nanoparticles, suggesting that labile Cu­(II) may influence the cell cycle regulation . Thus, we proposed that the heterogeneous resistance of algae at different cell cycle stages to Cu stress stems from their disparate sensitivities to the labile Cu­(II) pool.…”
Section: Results and Discussionmentioning
confidence: 72%
“…The elevated Cu ion levels were found to interfere with essential cellular processes, including mitochondrial function and signaling pathways, culminating in apoptosis or necrosis. 28 Moreover, the Cu could catalyze the production of reactive oxygen species (ROS) through Fenton-like reactions, 29 leading to oxidative stress, 30 cellular damage, and a disruption of homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme , these NRs could effectively ablate bacteria under 808 nm laser irradiation. In normal environments, CuAu NRs released fewer copper ions, however, which were largely released in the acidic infection microenvironment, further enhancing the antibacterial effect and improving re-epithelialization. We further proved the effectiveness of CuAu NRs in methicillin-resistant Staphylococcus aureus (MRSA) affected chronic wounds model in mice and MRSA-affected keratitis model in rabbits.…”
Section: Introductionmentioning
confidence: 99%